Investigation into gas dynamics in an oxyfuel coal fired boiler during master fuel trip and blackout. (May 2016) - Starkloff, Ralf; Postler, Ralf; Al-Maliki, Wisam Abed Kattea; Alobaid, Falah; Epple, Bernd
Highlights: First dynamic simulation of master fuel trip and blackout in an oxyfuel coal fired boiler. Reduction of the negative pressure amplitudes during a master fuel trip from −28 mbar to −21 mbar. Blackout scenario will not have any negative impact on designed oxyfuel coal fired boiler. Abstract: In an oxygen fired power plant, a large amount of flue gas is recirculated, leading to an unavoidable interaction between the involved fans. The presented paper investigates the dynamics of the gas side at different safety related scenarios. A dynamic simulation model is therefore developed to study the flue gas behaviour in an oxyfuel pulverized coal fired boiler during a master fuel trip and a blackout of the plant. The generated numerical model contains the water/steam side of the boiler, starting from economiser inlet and ending at the hot reheat outlet, and the gas side, including all relevant fans, convective heat exchangers, gas–gas heat exchangers and flue gas cleaning devices. Furthermore, a set of additional models for coast down behaviour of axial fans has been implemented. For the master fuel trip case, different relevant parameters of process control measures regarding the gas dynamics have been analyzed and an optimized master fuel trip scenario is proposed. The blackout of an oxyfuel coal fired boiler at nominal load is detailed demonstrated. The numerical results show that the blackout scenario will not have any negative impact on investigated gas part of the boiler system since the observed lowest negative furnace pressure of −36 mbar can be handled with current state of the art technology.